PENGARUH MANAGERIAL ABILITY, PROFITABILITAS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Tjahyadi, Levina; Marpaung, Elyzabet Indrawati (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
Tax aggressiveness is an activity that carried out to reduce a company’s tax profits which can be done through tax avoidance and tax evasion. The purpose of this study is to conduct testing and analysis that discusses the effect of managerial ability, profitability and leverage on tax aggressiveness. This research utilizes secondary data obtained from the official website of the sample company. This research uses purposive sampling technique. The sample in this study is 27 energy sector companies. The data analysis method used is SPSS. The results show that managerial ability has no effect on tax aggressiveness. It was also found that profitability has a positive influence on tax aggressiveness. In addition, it was found that leverage has a negative influence on tax aggressiveness.